Developing Ethnoecology-Based Digital IPAS Teaching Materials to Foster Pancasila Students in Madiun - Muhammad Hanif; Endang Sri Maruti (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The implementation of the Independent Curriculum (Kurikulum Merdeka) in Indonesia emphasizes flexibility, contextualization, and competency-based learning. However, many elementary school teachers, particularly in Madiun Regency, still rely on generic and non-digital materials that fail to represent local socio-ecological realities. This study aims to develop and validate digital teaching materials for Integrated Natural and Social Sciences (IPAS) based on Madiun’s ethnoecology to strengthen the Pancasila Student Profile. Using the Research and Development (R&D) approach adapted from Gall, Gall, and Borg (2007), the research involved students from grades I and IV in selected elementary schools through purposive sampling. Data were collected using expert validation sheets, teacher and student response questionnaires, and pre-test and post-test assessments. The results show that the developed materials are valid, practical, and effective in improving learning outcomes and fostering critical thinking, environmental awareness, and cooperative values. Students demonstrated increased engagement and conceptual understanding when interacting with digital modules that featured local wisdom such as farming traditions, forest management, and water conservation. Theoretically, this study contributes to the framework of culturally responsive and technology-integrated science education. Its novelty lies in combining IPAS, ethnoecology, digital learning, and Pancasila-based pedagogy, a synthesis that has rarely been explored, especially in elementary education. The findings suggest that integrating local ecological knowledge with digital pedagogy can enhance contextual, meaningful, and character-oriented learning experiences aligned with the goals of the Independent Curriculum.